The Role Of Finance Performance In Moderating The Effect Of Erm, Corporate Governance, CSR, And Sustainability Report On Firm Value - Melindah Seviona; Tantina Haryati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study was conducted with the aim of knowing the role of finance performance in moderating the Effect of ERM, Corporate Governance, CSR, and Sustainability Report on Firm Value. This study uses a population of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. This type of research is explanatory research with a quantitative approach. The data used is secondary data in the form of annual reports. The sampling method used was purposive sampling, which resulted in 48 manufacturing sector companies as research samples based on predetermined criteria. The analysis technique used is Partial Least Square (PLS) with the help of the Smart-PLS program. The results showed that ERM and CG have a positive and significant influence on firm value. However, CSR and SR do not have a significant influence on firm value. On the other side, finance performance is not able to moderate ERM, CSR and SR on firm value, but finance performance is able to moderate CG.